(untitled) (International Journal of Environmental Sciences, 2025)
Dünyada arts and cultural organizations succeed because of their strategic management abilities which create sustainable growth in uncertain environment This paper examines the strategic methods used by these organizations for managing financial limitations along with audience outreach together with policy adjustments and technological changes. The research examines the process through which arts institutions match their mission with tactical approaches while working with their stakeholders and responding to outside and inside obstacles. The research examines strategic planning activities in the cultural sector through systematic analysis of case evidence which reveals the most important success elements andencounters hurdles alongside current sector developments. The paper makes final recommendations which introduce cultural-specific frameworks alongside innovations and resilience strategies along with democratic governance approaches.